2018
DOI: 10.1002/prot.25477
|View full text |Cite
|
Sign up to set email alerts
|

The ω‐transaminase engineering database (oTAED): A navigation tool in protein sequence and structure space

Abstract: The ω-Transaminase Engineering Database (oTAED) was established as a publicly accessible resource on sequences and structures of the biotechnologically relevant ω-transaminases (ω-TAs) from Fold types I and IV. The oTAED integrates sequence and structure data, provides a classification based on fold type and sequence similarity, and applies a standard numbering scheme to identify equivalent positions in homologous proteins. The oTAED includes 67 210 proteins (114 655 sequences) which are divided into 169 homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…By assuming that evolution has reached an equilibrium in protein sequence space, the more evolvable folds might have become densely populated as a consequence of convergent evolution [ 42 ], thus connecting the concept of hubs to the concept of evolvability. The observation of a uniform distribution of sequences from thermophilic and hyperthermophilic sources in the oTA network demonstrated that hub sequences are not characterized by increased thermostability ( S2 Fig in [ 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…By assuming that evolution has reached an equilibrium in protein sequence space, the more evolvable folds might have become densely populated as a consequence of convergent evolution [ 42 ], thus connecting the concept of hubs to the concept of evolvability. The observation of a uniform distribution of sequences from thermophilic and hyperthermophilic sources in the oTA network demonstrated that hub sequences are not characterized by increased thermostability ( S2 Fig in [ 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Since activity has only been observed in growing cells, a cofactor-dependent mechanism is likely. Moreover, an additional transaminase would have been detected under the given conditions, and also a side activity of the identified ( S )-β-PA can be excluded: ( R ) and ( S )-ω-TAs show only low sequence identities and can clearly be differentiated by protein fold types (Höhne et al 2010 ; Buß et al 2018a ). A transamination of ( R )-β-PA would have led to the formation of AP, but on the contrary the concentration of AP decreased.…”
Section: Discussionmentioning
confidence: 99%
“…A standard numbering scheme was established for Classical and Extended SDRs to facilitate the identification of structurally and functionally equivalent positions, as it had been previously shown for other enzyme families . Crystal structures were selected to cover mostly all homologous families of Classical and Extended SDRs in the SDRED with known PDB entries.…”
Section: Methodsmentioning
confidence: 99%
“…Protein family databases are useful tools to study the relationship between sequence, structure, and function of enzymes and to support the design of novel enzymes . In this study, the Short‐chain Dehydrogenase/Reductase Engineering Database ( https://sdred.biocatnet.de/ .)…”
Section: Introductionmentioning
confidence: 99%